Click-Wrap Agreement: Pengalihan Tanggungjawab Dalam Melindungi Konsumen - Chusnida, Nabilah Luthfiyah (PROGRESIF: Jurnal Hukum, 2023)
click-wrap agreement is a form of agreement with a number of terms and conditions that include an agreement clause at the end of which there is a blank box with the sentence I Agree or I agree. The purpose of this study is to examine the validity and legal force of click-wrap agreements as electronic standard contracts. The approach method in this study is a normative juridical approach with the research specifications used namely descriptive-analytical with data collection techniques through legal materials in the form of secondary data, namely laws and regulations and literature. The data obtained was then processed and analyzed using qualitative methods. The results of the study show that currently there are several forms of electronic contracts, one of which is the click-wrap agreement. In a commercial transaction, before offering its product by displaying the terms and conditions, consumers are expected to read further beforehand. Then the consumer agrees to these terms and conditions by clicking on the box contained in the sentence "I Agree" or I agree. The validity of the click-wrap agreement basically refers to the Civil Code and UUPK regarding the transfer or limitation of responsibility.